2005
DOI: 10.1143/jjap.44.4770
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Fabrication of Polycrystalline Si Thin Film Using Al-Induced Crystallization without Native Al Oxide at Amorphous Si/Al Interface

Abstract: Low-temperature fabrication of polycrystalline silicon (poly-Si) thin film has been performed by Al-induced crystallization (AIC), and the structural properties have been investigated. In our experiments, to prevent native oxidation of Al film, an amorphous silicon (a-Si)/Al bilayer was formed on the SiO2/Si substrate by electron beam evaporation without breaking the vacuum. The a-Si/Al/SiO2/Si structure was then heated at a low temperature of 400°C to induce AIC. It was confirmed that layer exchange of the a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 21 publications
(27 reference statements)
4
64
0
Order By: Relevance
“…Figure 2 (b) also shows that the grain size of the AIC poly-Si layer prepared from the same a-Si and Al thickness is larger than 10 m. This result is in good agreement with the previously reported results 20 . Figure 3 shows Raman spectra of AIC poly-Si layers prepared at a temperature ranging from 450 to 525 o C. The thicknesses of the a-Si and Al are 200 nm.…”
Section: Fabrication Of An Aic Poly-si Layer and A Poly-si Film On Thsupporting
confidence: 94%
“…Figure 2 (b) also shows that the grain size of the AIC poly-Si layer prepared from the same a-Si and Al thickness is larger than 10 m. This result is in good agreement with the previously reported results 20 . Figure 3 shows Raman spectra of AIC poly-Si layers prepared at a temperature ranging from 450 to 525 o C. The thicknesses of the a-Si and Al are 200 nm.…”
Section: Fabrication Of An Aic Poly-si Layer and A Poly-si Film On Thsupporting
confidence: 94%
“…On the other hand, growth of (111)-oriented Si layers has been also reported [15,18]. Kurosawa et al showed that the preferential orientation of AIC-Si on fused silica can be controlled by changing the exposure time of Al in air, and they proposed a model showing that the orientation of AIC-Si is determined by the crystal phase of the native Al oxide [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Si, isothermal annealing of amorphous Si (a-Si)/Al layers on glass at temperatures below the eutectic temperature (577 1 C) results in layer exchange and formation of a continuous polycrystalline Si thin film [2][3][4][5].The preferential growth orientation is known to be either /1 0 0S or /1 1 1S depending on growth conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%